Editorial: Vascular dysfunction beyond pathological pregnancies. An international effort addressed to fill the gaps in Latin America - Giachini, Fernanda (2019)
Pregnancy is a physiologically stressful condition that generates a series of functional adaptations in the cardiovascular system. Recent evidence suggests that vascular changes associated with pregnancy complications may impair the function of the maternal and offspring vascular systems after delivery, being possibly extended until adult life. In Latin American countries, like other low (LIC) and middle-income countries (MIC) worldwide, the rate of morbi-mortality due to both pregnancy complications and cardiovascular diseases have a higher incidence than in high-income countries. Paradoxically, research in this field is limited in Latin America (Giachini et al., 2017). Then, in addition to the scientific and public health implications of the maternal morbi-mortality in LIC and MIC, we also aimed to overcome geographic limitations. Therefore, our research topic titled Vascular Dysfunction Beyond Pathological Pregnancies. An International Effort Addressed to Fill the Gaps in Latin America intends to positively contribute in the scientific field, but also to visualize the challenging need for more investigation in our countries.